Consolidated Regulation and Supervision in the United States - Bhatia, Ashok (IMF Working Papers; Working Paper, 2011)
This paper builds on a Technical Note produced as part of the IMF's 2010 Financial Sector Assessment Program (FSAP) review of the United States. It addresses enterprise-wide oversight of financial groups, a key tool to mitigate systemic risk. Focusing on legal arrangements, it recommends eliminating exceptions for holding companies owning certain limited-purpose banks, harmonizing arrangements for bank and thrift holding companies, and bringing into the net a few systemic nonbank financial groups, with the Federal Reserve as the sole consolidated regulator and supervisor.